Tuberculosis and diabetes mellitus: Relating immune impact of co-morbidity with challenges in disease management in high burden countries. (December 2022) - Abbas, Uzair; Masood, Kiran Iqbal; Khan, Aalia; Irfan, Muhammad; Saifullah, Nausheen; Jamil, Bushra; Hasan, Zahra
Abstract: Mycobacterium tuberculosis (MTB) is the causative agent of TB. TB incidence is high in many low resource settings where limited health systems make it difficult for screening of co-morbid conditions. Susceptibility to TB is increased with coincident diabetes mellitus (DM) or prediabetes. DM leads to chronic, subclinical inflammation in the host leading to compromised protective immunity against MTB, impacting TB treatment. This review focuses on the immunological impact of DM and prediabetes on TB infections, highlighting the importance of having effective diagnostic, treatment and management programs for early identification of hyperglycemia in TB patients to improve treatment outcomes. Further, it describes challenges in monitoring of TB and DM co-morbidity in a high-burden setting.